A proposed assessment tool for measuring the spatial accessibility of libraries in the Philippines using enhanced 2-step floating catchment area (a GIS-based method) - Hernandez, Luke Martin
This study introduces a proposed GIS-based assessment tool designed to measure the spatial accessibility of libraries in the Philippines, leveraging the Enhanced Two-Step Floating Catchment Area (E2SFCA) method. Originally developed for healthcare accessibility, the E2SFCA method is adapted in the study to evaluate library services, recognizing libraries as vital community hubs. The E2SFCA method assesses whether library services are sufficient for the population served by the libraries while giving weight to nearer populations over farther ones.